DINAMIKA PSIKOLOGIS RESISTANCE TO CHANGE TERHADAP BANKING PAYROLL - , Aad Satria Permadi, Prof. Dr. Faturochman, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Banking payroll is a beneficial payroll system when itâs viewed from the nature of efficiency and transparency. However, some people reject the system. This has led to the slow of organizational performance, and vulnerability of financial fraud. This study tried to uncover the causes of these rejections in TK ABA Nitikan Yogyakarta. The method of this study is phenomenology. Participants consisted of five teachers of TK ABA Nitikan, who have different attitudes. Three people refused banking payroll, while others accept it. There are two types of rejections